The exponential variation of heated extending sheet in casson fluid flow - Ahmad, Kartini; Mohamed Isa, Siti Suzilliana Putri (UPM Press, 2019)
The mathematical model of the following case is developed: The magnetohydrodynamics (MHD) of Casson fluid flow with heated at the surface due to Newtonian heating. This study takes into account in a concentrated Casson fluid flow with existence of thermal radiation. Similarity transformation is used, to convert the governing equations (continuity, momentum, energy, mass diffusion equations) into ordinary differential equations (ODE). Later on, these ODE is determined by applying the finite-difference method. The profiles of velocity, temperature, concentration and concentration gradient are depicted for certain values of controlling parameters. The consenquences of the controlling parameters on the system are described in details.